Civil society aid as balancing act – navigating between managerial and social transformative principles. Issue 6 (17th August 2020) - Kamstra, Jelmer
ABSTRACT: The civil society policy of the Ministry of Foreign Affairs of the Netherlands shifted from service delivery to lobby and advocacy in 2016 with the new Dialogue & Dissent policy framework (D&D), representing a large change in thinking from a managerial to a social transformative perspective. This article discusses how D&D has made this shift and navigates tensions arising from it: (1) by stressing the political role of CSOs; (2) by working in strategic partnerships; and (3) by employing flexible Theories of Change focused on learning. It concludes with lessons learnt for D&D's successor.